Using patterned substrates to promote mixing in microchannels. - Kuksenok, O; Yeomans, J; Balazs, A (2002)
Using a lattice Boltzmann model for fluid dynamics, we investigate the flow and phase behavior of a binary fluid moving over a patterned substrate within a microchannel. The binary fluid consists of two immiscible components, A and B, and this liquid is subjected to a Poiseuille flow. The substrate is decorated with a checkerboard pattern of A- and B-like patches. Through a coupling of hydrodynamics and thermodynamics, each component is driven to flow from the nonwettable domains to wettable regions. As a consequence, the A and B fluids undergo extensive mixing within the microchannels. We investigate how the degree of mixing depends on the size of the patches, the velocity of the imposed flow field, and the characteristics of the fluid. The results provide guidelines for creating localized "mixing stations" within microfluidic devices. The findings also reveal how a combination of imposed flow fields and surface patterning can be exploited to control the phase behavior of complex fluids.